The Widespread Use of Slang and Abbreviations Among Youth On Social Media - Xursanovna, Umurzakova (CONVERSE Journal Communication Science, 2025)
This article explores the widespread use of slang and abbreviations among youth in social networks and their impact on language development and communication. While slang and abbreviations serve as tools for quick interaction among youth, they can negatively affect literary language and deepen generational linguistic gaps. The study provides solutions and recommendations based on the findings. This study examines the widespread use of slang and abbreviations among youth on social media, analyzing their linguistic, social, and cultural impacts. A mixed-methods approach was employed, including surveys (150 participants aged 18–25), interviews, qualitative and quantitative analysis, and document review. Results indicate that while slang enhances communication efficiency and social bonding, excessive usage degrades literary language standards and intergenerational communication. Although 62% of participants use slang in formal settings, 68% believe it contributes to language deterioration. The study concludes that balancing slang use with literary language preservation is crucial for maintaining linguistic and cultural integrity.